Laughter in national sorrows. On the margins of reading Polish satirical writings published in Lvov in the second half of the 19th century - Załęczny, Jolanta (Laughter, humour, satire, 2024)
The 19th century was a period of intensified independence efforts, which ended – unfortunately – in defeats. Intensified Russification and Germanization, as well as repression by the partitioning authorities, were to break the Poles. The antidote to national sorrows became humor, the manifestations of which could be found in the pages of the press. Newspaper titles coming out in Galicia show a wide spectrum of topics and modes of communication. Reading selected satirical writings gives an answer to the question of what Poles laughed at in the second half of the 19th century.